Bahan Ajar Berbasis Etnosains Pada Pembelajaran Tematik Terpadu di Kelas V Sekolah - Fauzana Nelmi; Risda Amini (Elementary Teacher Education Program, Majalengka University, 2023)
Students have difficulty in understanding learning materials at school because of the unavailability of teaching materials that can help students to link learning materials with the surrounding environment and teachers have not utilized ethnoscience in learning. This causes the learning objectives not to be achieved optimally. Ethnoscience-based teaching materials are one of the teaching materials that can help students to easily understand learning materials because they present learning that is closer to the culture and environment of students. Therefore, this study raised the title of the development of ethnoscience-based teaching materials on integrated thematic learning in grade V elementary school. This research uses the R&D (Reaserch and Development) approach with the 4-D model to develop ethnoscience-based teaching materials on integrated thematic learning in grade V SD that are valid and practical. The results obtained from this study were 94% with a very valid category from 3 aspects, namely, material experts, presentation experts and linguists. The results of the practicality test in the research school were 92.8% for teacher responses and 92.8% for student responses. Thus, the use of ethnoscience-based teaching materials in integrated thematic learning in grade V SD is valid and practical for use in the learning process